Desarrollo de una aplicación Android para anunciar la presencia de sobrevivientes mediante un botón de pánico (2021)
Natural disasters have been increasing over the years around the world. The environment has been affected by the actions of man, who has exploited natural resources and deteriorated nature without control. When a catastrophic event occurs, and depending on the degree of preparedness of the population where the event occurs, it is possible that the event has dire consequences for a part of the inhabitants of the affected region.